2020
DOI: 10.1002/jobm.201900586
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial growth, morphology, and cell component changes in Herbaspirillum sp. WT00C exposed to high concentration of selenate

Abstract: Selenium (Se) is a nonmetallic element of the chalcogens. It is primarily available in natural environments as selenate and selenite oxoanions. Although selenate/selenite reduction in many microbes is widely studied at low concentrations (<50 mM), the effects of high selenate stress on bacterial growth, morphology, and cell components have not yet been studied. In this study, the response of Herbaspirillum sp. WT00C to selenate stress at high concentration is investigated by microbiological and scanning electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 50 publications
1
6
0
Order By: Relevance
“…The strains CT00C and NCT00C displayed 10-fold less expression, whereas the strain NT00C increased 7 folds as compared to the strain WT00C. Less transcription of lpxB gene suggested that the activity of lpxB gene was seriously inhibited by high concentration of selenate, which was in accord with the results observed in the previous study [34] . Nevertheless, the expression of lpxB gene was gradually increased along with the increase of exposure times in selenate as shown in Fig.…”
Section: Transcriptional Levels Of the Genes Involving In Selenate Me...supporting
confidence: 90%
See 3 more Smart Citations
“…The strains CT00C and NCT00C displayed 10-fold less expression, whereas the strain NT00C increased 7 folds as compared to the strain WT00C. Less transcription of lpxB gene suggested that the activity of lpxB gene was seriously inhibited by high concentration of selenate, which was in accord with the results observed in the previous study [34] . Nevertheless, the expression of lpxB gene was gradually increased along with the increase of exposure times in selenate as shown in Fig.…”
Section: Transcriptional Levels Of the Genes Involving In Selenate Me...supporting
confidence: 90%
“…When bacterial cells grew in the medium containing selenate or selenite, red color formation in the culture indicated the generation of red elemental selenium (Se 0 ) [29,33,34] . As shown in Fig.…”
Section: Red Elemental Selenium (Se 0 ) Formation Of Four Different S...mentioning
confidence: 99%
See 2 more Smart Citations
“…Surgery can remove the lesion tissue, prolong the life of patients, and quickly improve their symptoms [5]. However, due to the lack of effective evaluation methods in perioperative period of some GC patients, the long-term prognosis of patients is relatively long [6]. Tumor mutation burden (TMB) is defined as the total number of somatic coding errors, base substitutions, gene insertion, or deletion errors detected per million bases, which can be obtained by the NGS method.…”
Section: Introductionmentioning
confidence: 99%